Perbandingan Hukum Perdata Tentang Orang dan Badan Hukum di Indonesia, Amerika dan Inggris - Rafidah, Annisa Rahma; Nurrachman, Azzahra (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Legal subjects are anything that can obtain rights and obligations from the law. Legal subjects are bearers of rights or subjects in law, namely people. Legal entities are legal subjects that do not have souls like humans, so that legal entities cannot carry out legal acts themselves, but are represented by ordinary humans and the person acts not as themselves, but on behalf of the legal entity. Descriptive research methods focus on collecting and analyzing data to provide a clear picture of a phenomenon or situation. Descriptive-analytical research is more specific, because in addition to describing phenomena, this method also analyzes the relationship or association between variables. By comparing the law in Indonesia with the law in other countries, we can have a new outlook on life. Although there are differences in the legal systems of each country, humans still have the same rights and obligations in the eyes of the law.